The factors affecting purchase intention of organic foods in Vietnam market - Pham, Quynh Trang (H. : ĐHQGHN, 2020)
This research helps find out the factors affecting purchase intention of organic food in Vietnam market. The results shows that there are three affecting factors: Health consciousness, safety concern and shopping habit. Among these factors, food safety concern has the biggest impact on purchase intention.